A novel approach for cumulative impacts assessment for marine spatial planning. Issue 106 (April 2020) - Lonsdale, Jemma-Anne; Nicholson, Rose; Judd, Adrian; Elliott, Michael; Clarke, Charlotte
Highlights: The development of a practical marine Cumulative Effect Assessment (CEA) approach. The development of a tool to demonstrate the CEA approach. The use of the CEA approach and tool in marine environmental decision making. Where there are gaps in knowledge and data, shows further elaboration required. Whilst presented for the UK, the approach can be applied worldwide. Abstract: The assessment of the cumulative impacts of multiple human activities is an increasingly important yet complex part of managing the marine environment. Despite this, as yet, there is no consistent approach to considering these in assessments and/or management (e.g. environmental impact assessment, marine spatial planning). Current and previous approaches to the assessment of cumulative impacts have limitations and shortcomings e.g. double counting of impacts or avoiding, complicating and confounding impacts, which need to be addressed to allow for pragmatic decisions to be made. Here, an innovative, practical approach to marine CIA is presented that considers the three dimensional nature of the marine environment, and the spatial and temporal effects-footprints likely to occur during the lifetime of a development. The new approach is tested within a GIS platform and shows an effective visual representation for decision makers, managers and policy makers on which to base their decisions. While showing potential, the approach indicates the need to incorporate temporal data and assessing temporal trends. Despite this limitation, the tool markedly improves on previous approaches due to the national and practical application, and the incorporation of 3D nature of pressures and receptors.